RADIATION RISKS ASSESSMENT DUE TO CONSUMPTION OF THE FAR EAST FOOD FISH AFTER THE ACCIDENT ON “FUKUSHIMA-1” NPP - G. G. Onishсhenko; V. S. Repin; I. K. Romanovich (Радиационная гигиена, 2015)
The paper presents a review of the data on radioactivity releases to thePacific Oceanlevels after the Fukushima NPP accident. It is shown that the potential risk of of the seafood contamination with the long-living radionuclides 134Cs and 137Cs, which continue to be released to the Pacific Ocean up to the present time. Contribution of 90Sr to the total radioactive contamination does not exceed 3%. Review of the literature data on the modeling of radioactivity spot diffusion showed that due to the flows in the Pacific Ocean the radioactivity transfer toKamchatka Peninsula, the Kuril Islands, and the ingress into theOkhotskSeawas expected in 2014. It is expected a slight increase of the cesium concentration in water and sea biota in the area of Russia fishing zone FAO 61, but not higher than the concentrations in the Black Sea and Baltic Sea after the Chernobyl accident. Data on measurements of the pollution of fish caught in the Pacific Ocean,JapanandOkhotskSeasin 2011–2014 years during the sea expeditions organized by the Russian Geographical Society, yet showed that the total content of cesium isotopes in any fish sample have not eceeded the value of 0.7 Bq/kg. The prognose risk assessment carried out for the conservative scenario of water contamination in fishing zones ofRussiaand seafood consumption characteristic for the region showed that this risk is minimal according to the WHO scale and does not exceed the risk from fish caughed in Black Sea and Baltic Sea, contaminated after theChernobylaccident, consumption.